Comparison of acute respiratory distress syndrome in patients with COVID-19 and influenza A (H7N9) virus infection. (September 2022) - Ding, Ling; Chen, Yikun; Su, Nan; Xu, Xizhen; Yin, Jingping; Qiu, Jun; Wang, Jiajia; Zheng, Dong
Highlights: Patients with H7N9- acute respiratory distress syndrome (ARDS) showed a more acute disease course and severity. Disseminated intravascular coagulation was more common in patients with COVID-19-ARDS. The main causes of death between H7N9-ARDS and COVID-19-ARDS were different. This is the first study to compare clinical features between the two diseases. Abstract: Objectives: We aimed to compared the clinical features of acute respiratory distress syndrome (ARDS) induced by COVID-19 and H7N9 virus infections. Methods: Clinical data of 100 patients with COVID-19 and 46 patients with H7N9 were retrospectively analyzed. Results: Elevated inflammatory indices and coagulation disorders were more common in COVID-19-ARDS group than in the H7N9-ARDS group. The median interval from illness onset to ARDS development was shorter in H7N9-ARDS. The PaO2 /FiO2 level was lower in H7N9-ARDS, whereas the Sepsis-related Organ Failure Assessment score was higher in COVID-19-ARDS. The proportion of patients with disseminated intravascular coagulation and liver injury in COVID-19-ARDS and H7N9-ARDS was 45.5% versus 3.1% and 28.8% versu s 50%, respectively ( P <0.05). The mean interval from illness onset to death was shorter in H7N9-ARDS. A total of 59.1% patients with H7N9-ARDS died of refractory hypoxemia compared with 28.9% with COVID-19-ARDS ( P  = 0.014). Patients with COVID-19-ARDS were more likely to die of septic shock and multiple organ dysfunction compared with H7N9-ARDS (71.2% vs 36.4%, P  = 0.005). Conclusion: Patients with H7N9 were more susceptible to develop severe ARDS and showed a more acute disease course. COVID-19-ARDS was associated with severe inflammatory response and coagulation dysfunction, whereas liver injury was more common in H7N9-ARDS. The main causes of death between patients with the two diseases were different.